Sime Darby goes to Liberia. - Sulaiman, Mohamed; Zandi Pour Joopari, GholamReza; A. Rahman, Akmal Nurhananie (Management Centre, IIUM, 2011)
This case study discusses the issues arising from Sime Darby Corporation being given a concession agreement to develop 220,000 hectares of land with palm and rubber plantations in Liberia for a period of 63 years. Sime Darby Bhd is a Malaysian multinational company with diverse interests. Its main focus is plantations with its major crops being oil palm and rubber. It has large plantations in Malaysia and Indonesia. With land becoming scarce in Southeast Asia, Sime Darby looked for opportunities in Africa. They found a partner in Liberia which needed foreign investment to revive its economy after two civil wars. While the opportunities looked great on papers, questions arose over the risks involved.